Analysis of Heat and Smoke Flow according to Platform Screen Door and Fan Conditions on Fire in Underground Platform - Ju-Yeong Jung; Seung-Gu Kang; Hyuk-Jin Yoon; Kwang-Bok Shin; Jong-Kwang Lee (Advances in Civil Engineering)
In this study, a three-dimensional flow analysis of underground subway station was conducted by applying ventilation mode in operation and platform screen door (PSD) opening and closing conditions on fire in underground platform. In order to analyze optimal smoke control and heat removal conditions, the whole underground subway station was set as a model, and a total of eight cases were analyzed by changing the operating conditions of fans for each area under the opening and closing conditions of the PSDs. The analysis results confirmed that the operation mode of supply fan in platform E and I areas located at the third floor underground is more effective than that of exhaust fan in the event of a fire in underground subway station when the PSD is closed. The amount of CO entering a waiting room increased, and the overall CO distribution in the underground subway station was also increased when the PSD is opened. In addition, the CO distributions due to the opening and closing of the PSD were similar to one another when a fire occurred on the platform, which suggests that the operating conditions of the fan affects the formation of CO distribution in the underground subway station rather than the discharge of CO.